Market orientation in higher education and innovativeness as a mediating variable - Algarni, Abdullah Mohammed M. (2015)
Market orientation (MO) is an operationalization of a marketing concept and considered vital to enhance organization profitability and sustainability especially for businesses. However, efforts to investigate MO in the educational context have not been extensively conducted in comparison to those in the business settings. This research assessed the influence of top management emphasis and internal market orientation (IMO) as antecedents to MO in higher education institutions (HEIs). It also examined the effect of IMO and MO on HEIs perceived performance. In addition, the mediation role of innovativeness to the relationship of MO and perceived performance was investigated. The unit of analysis in this research was an educational institution that provides tertiary education under the supervision of the Ministry of Education in Saudi Arabia. In this quantitative cross sectional study, the whole population was targeted and data was collected online. There were 263 usable responses from 537, representing 48.97% response rate. The findings of this research indicated that there is a positive relationship between top management emphasis and IMO, as well as with MO. Results also showed that IMO was found to be positively related to MO. On the contrary, the relationship between IMO and HEIs perceived performance was found to be insignificant. Besides that, the study disclosed that MO is positively related to HEIs perceived performance. In this study, innovativeness was found to be partially mediating the relationship between MO and perceived performance. The research has illustrated the application of MO in the educational setting of a developing country. Additionally, the findings of the study will help academic managers and education policy makers in Saudi Arabia to develop market oriented strategies to improve HEIs performance.